Mesoporosity in doped silicon nanowires from metal assisted chemical etching monitored by phonon scattering. (1st October 2015) - McSweeney, William; Glynn, Colm; Geaney, Hugh; Collins, Gillian; Holmes, Justin D; O'Dwyer, Colm
Abstract: Si nanowires (NWs) are shown to develop internal mesoporosity during metal assisted chemical etching from Si wafers. The onset of internal porosity in n + -Si(100) compared to p-Si(100) is examined through a systematic investigation of etching parameters (etching time, AgNO3 concentration, HF % and temperature). Electron microscopy and Raman scattering show that specific etching conditions reduce the size of the internal Si nanocrystallites in the internal mesoporous structure to 3–5 nm. Mesoporous NWs are found to have diameters as large as 500 nm, compared to ∼100 nm for p-NWs that develop surface roughness. Etching of Si (100) wafers results in (100)-oriented NWs forming a three-fold symmetrical surface texture, without internal NW mesoporosity. The vertical etching rate is shown to depend on carrier concentration and degree of internal mesoporosity formation. Raman scattering of the transverse optical phonon and photoluminescence measurements confirm quantum size effects, phonon scattering and visible intense red light emission between 685 and 720 nm in internally mesoporous NWs associated with the etching conditions. Laser power heating of NWs confirms phonon confinement and scattering, which is demonstrated to be a function of the internal mesoporosity development. We also demonstrate the limitation of mesoporosity formation in n + -Si NWs and development of porosity within p-Si NWs by controlling the etching conditions. Lastly, the data confirm that phonon confinement and scattering often reported for Si NWs is due to surface-bound and internal nanostructure, rather than simply a diameter reduction in NW materials.